2010
DOI: 10.1243/09544054jem1825
|View full text |Cite
|
Sign up to set email alerts
|

Finite element method study of incremental sheet forming for complex shape and its improvement

Abstract: In order to improve the incremental sheet forming process for the product of complex shape (e.g. human face), a combination of both computer-aided manufacturing (CAM) and finite-element modelling (FEM) simulation, is implemented and evaluated from the histories of stress and strain value by means of finite-element analysis. Here, the results, using ABAQUS/Explicit finite-element code, are compared with forming limit curve at fracture in order to predict and improve the forming conditions by changing process va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…But, recently studies have shown that ISMF process achieved greater formability and FLC shape almost like a straight line with negative slope in the principal limit strains (major strain, ε1, and minor strain, ε2). In order to estimate the forming limit curve at fracture (FLCF) in ISMF for a cold rolled, Nguyen et al [3] proposed the combination method for predicting FLC based on in-plane test (M-K model) and ductile fracture criterion of Clift et al [4]. In the previous study [5], cold rolled steel sheet improved formability by ISMF process and is also used to manufacture automotive structure [6] as shown in Figure 4.…”
Section: Incremental Sheet Metal Forming 21 Basic Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…But, recently studies have shown that ISMF process achieved greater formability and FLC shape almost like a straight line with negative slope in the principal limit strains (major strain, ε1, and minor strain, ε2). In order to estimate the forming limit curve at fracture (FLCF) in ISMF for a cold rolled, Nguyen et al [3] proposed the combination method for predicting FLC based on in-plane test (M-K model) and ductile fracture criterion of Clift et al [4]. In the previous study [5], cold rolled steel sheet improved formability by ISMF process and is also used to manufacture automotive structure [6] as shown in Figure 4.…”
Section: Incremental Sheet Metal Forming 21 Basic Conceptsmentioning
confidence: 99%
“…(2), (3), and (5). Figure 7 depicts the forming limit curves in ISMF based on the forming limit curves of the traditional method (V-shaped) for various experimental forming tools [3].…”
Section: Formability Of Ismfmentioning
confidence: 99%
See 1 more Smart Citation
“…However, extensive research has shown that not only are much higher strains achieved in this process, but the FLC in ISF has a negative slope. Nguyen et al 3 combined the prediction of forming limit curve at necking (FLCN) in conventional forming based on in‐plane test (M‐K model) and the ductile fracture criterion of Clift et al 4 to estimate the forming limit curves at fracture (FLCF) in ISF for a cold rolled steel as shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, FEM simulation is used as an essential tool for understanding, predicting and improving the performance of various sheet forming processes such as stretching hydro‐forming 13, 14, stamping 15, deep‐drawing 16, and incremental forming 3, 12 etc., it is primarily used to clarify the forming characteristics and prevent forming defects. However, commercial software is inconvenient to simulate an incremental forming process for a complex shape because the various programs only support simple movements such as linear or circular motions.…”
Section: Introductionmentioning
confidence: 99%